P034 Assessment of age as a risk factor for adverse events in patients from the tofacitinib ulcerative colitis clinical program. (July 2019) - Gary, Lichtenstein; Brian, Bressler; Gary, Chan; Chinyu, Su; Gary, Friedman; Nervin, Lawendy; Ronald, Pedersen; Leonardo, Salese; Edward, Loftus
Abstract : BACKGROUND: Tofacitinib is an oral, small molecule JAK inhibitor for the treatment of ulcerative colitis (UC). Safety and efficacy of tofacitinib were demonstrated in Phase (P) 2/3 induction studies (NCT00787202; NCT01465763; NCT01458951), a 52-week, P3 maintenance study (NCT01458574), and are being further investigated in an ongoing, open-label, long-term extension (OLE) study (NCT01470612). This analysis assessed age as a risk factor for adverse events (AEs) in the tofacitinib UC clinical program. METHODS: Analyses of AEs were performed for 2 cohorts: the Maintenance Cohort (patients who received placebo or tofacitinib 5 or 10 mg twice daily in the maintenance study) and the Overall Cohort (all tofacitinib-treated patients in the P2/P3/OLE studies [as of December 2016]), stratified by age (≥65 years vs <65 years). AEs of special interest included serious infections (SIs), opportunistic infections (OIs), herpes zoster (HZ), malignancies (excluding non-melanoma skin cancer [NMSC]), NMSC, major adverse cardiovascular events (MACE), and gastrointestinal perforations. Risk factors (based on baseline characteristics) for SIs, OIs, HZ, and NMSC in the Overall Cohort were evaluated using multivariate Cox proportional regression models. RESULTS: AEs occurred in 75.3% (placebo) and 75.9% (tofacitinib) of patients in the Maintenance Cohort, and 82.1% in the Overall Cohort (in which 83.9% received predominantly tofacitinib 10 mg twice daily). Most patients (Maintenance Cohort: 180/198 [90.9%] and 364/394 [92.4%] receiving placebo and tofacitinib, respectively; Overall Cohort: 1, 080/1, 157 [93.3%]) were aged <65 years. In both the placebo and tofacitinib groups of the Maintenance Cohort, rates of AEs, serious AEs, severe AEs, and discontinuations due to AEs were numerically higher in patients aged ≥65 years (placebo: 83.3%, 11.1%, 11.1%, and 22.2%; tofacitinib: 80.0%, 16.7%, 10.0%, and 16.7%) vs <65 years (placebo: 74.4%, 6.1%, 9.4%, and 18.3%; tofacitinib: 75.5%, 4.4%, 7.1%, and 8.8%). AEs of special interest were generally infrequent in both the placebo and tofacitinib groups of the Maintenance Cohort. In the Overall Cohort, AE, serious AE, and severe AE rates were numerically higher in patients aged ≥65 years (88.3%, 19.5%, and 15.6%) vs <65 years (81.7%, 14.3%, and 12.2%). OI, HZ, malignancies (excluding NMSC), NMSC, and MACE rates were numerically higher in patients aged ≥65 years (3.9%, 14.3%, 2.6%, 5.3%, and 2.6%) vs <65 years (1.7%, 5.0%, 0.6%, 0.7%, and 0.2%); SI and gastrointestinal perforation rates were similar between age groups (≥65 years: 2.6% and 0.0%; <65 years: 2.9% and 0.4%). In multivariate modeling in the Overall Cohort, increasing age (every 10 years) was associated with increased risk of OIs (hazard ratio [95% confidence interval] 1.54 [1.15, 2.08]) and HZ (1.58 [1.34, 1.87]), but not SIs or NMSC (univariate modeling: 1.0 [0.78, 1.27] and 2.31 [1.46, 3.66]). CONCLUSION(S): In the tofacitinib UC program, AE rates were higher among patients aged ≥65 years vs those aged <65 years, regardless of whether they received tofacitinib or placebo. In multivariate analyses, older age was associated with increased OI and HZ risk. Although this is consistent with the general population, due to the small number of patients aged ≥65 years (<10% of the total), these findings should be interpreted with caution.